(untitled) (Third Sector Social Economic Review, 2020)
The question of the source and the nature of the political authority in the state established with the arrival of the Muhammadan invitation and what element this authority is based on, continues to occupy the mind of the thinkers who are studying, researching and reading on Islamic political thought. In this context, the question, which was formulated in the first Arab-Islamic state, by which element the political authority of the ruler was based on, aims to contain a general understanding of the source and quality of political authority in Islamic thought. The question of whether the source and the nature of the political authority in the period of the “founding experience”, which started with Muhammad and ended with the death of Ali, is based on a religious principle or a non-religious element, continues to be alive among today’s Muslims.In this study, Ibn Khaldun, who provides valuable clues based on relations between asabiyyah, religious invitation and state, will be applied although it is known that he is not in the effort to seek direct answer to such a problem. Thus, we will try to analyze whether the political authority is based on a religious or non-religious element in the first Arab-Islamic state under Ibn Khaldun’s guidance, approaching the question from its own perspective.